Mutational analysis of the 5′-OH oligonucleotide phosphate acceptor site of T4 polynucleotide kinase - Wang, Li Kai (Oxford University Press, 2010)
T4 polynucleotide kinase/phosphatase (Pnkp) exemplifies a family of bifunctional enzymes with 5′-kinase and 3′-phosphatase activities that function in nucleic acid repair. The N-terminal kinase domain belongs to the P-loop phosphotransferase superfamily. The kinase is distinguished by a tunnel-like active site with separate entrances on opposite sides of the protein for the NTP phosphate donor and a 5′-OH single-stranded oligonucleotide phosphate acceptor. Here, we probed by mutagenesis the roles of individual amino acids that comprise the acceptor binding site. We thereby identified Glu57 as an important residue, by virtue of its participation in a salt bridge network with two catalytic residues identified previously: Arg38, which binds the 3′-phosphate of the terminal 5′-OH nucleotide, and the putative general base Asp35 that contacts the nucleophilic 5′-OH group. The 5′-OH nucleoside fits into a pocket lined by aliphatic amino acids (Val131, Pro132 and Val135) that make van der Waals contacts to the nucleobase. Whereas subtraction of these contacts by single alanine substitutions for Val131 or Val135 and glycine for Pro132 had modest effects on kinase activity, the introduction of bulkier phenylalanines for Val131 and Val135 were deleterious, especially V131F, which severely impeded both substrate binding (increasing K(m) by 15-fold) and catalysis (decreasing k(cat) by 300-fold).